2005
DOI: 10.1080/00131880500104366
|View full text |Cite
|
Sign up to set email alerts
|

Security measures on school crime in Texas middle and high schools

Abstract: This statewide study surveyed 215 principals of middle schools and high schools in Texas, USA. It examined the effectiveness of activities on school crime by three main methods:(1) what activities the school was doing to combat crime (e.g. police/guards, school uniforms, metal detectors, drug education programmes, character education programmes, closed campus, surveillance, student court activity, rewards for attendance, etc.); (2) cooperation with outside sources (i.e. police, parents, school district, judici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 11 publications
1
14
1
Order By: Relevance
“…Studies incorporating multiple crime prevention techniques have also identified several variables as predictors of reduction in school violence including limited class changes (O'Neill & McGloin, 2007), closed campuses (O'Neill & McGloin, 2007), dress codes (Phillips, Turner, & Holt, 2014), identification cards (Phillips et al, 2014), security cameras (GranbergRademacker, Bumgarner, & Johnson, 2007), and uniform policies (Granberg-Rademacker et al, 2007). However, most studies focusing on the effectiveness of school situational crime prevention methods have found few statistically significant effects on violence occurring within the school (Chen, 2008;Cheurprakobkit & Bartsch, 2005;Schreck, Miller, & Gibson, 2003;Tillyer et al, 2011). These conflicted findings are mirrored by the divided viewpoints of administrators (Garcia, 2003) and students (Brown, 2005) about the effectiveness and appropriateness of crime prevention methods employed in the school setting.…”
Section: School Securitymentioning
confidence: 68%
“…Studies incorporating multiple crime prevention techniques have also identified several variables as predictors of reduction in school violence including limited class changes (O'Neill & McGloin, 2007), closed campuses (O'Neill & McGloin, 2007), dress codes (Phillips, Turner, & Holt, 2014), identification cards (Phillips et al, 2014), security cameras (GranbergRademacker, Bumgarner, & Johnson, 2007), and uniform policies (Granberg-Rademacker et al, 2007). However, most studies focusing on the effectiveness of school situational crime prevention methods have found few statistically significant effects on violence occurring within the school (Chen, 2008;Cheurprakobkit & Bartsch, 2005;Schreck, Miller, & Gibson, 2003;Tillyer et al, 2011). These conflicted findings are mirrored by the divided viewpoints of administrators (Garcia, 2003) and students (Brown, 2005) about the effectiveness and appropriateness of crime prevention methods employed in the school setting.…”
Section: School Securitymentioning
confidence: 68%
“…With that in mind, it is important to mention that the findings for this investigation coincided with the few empirical studies that used data from multiple schools to evaluate numerous policies through aggregate analyses. Despite variant methodological specifications, the pattern of insignificance of these tactics was widespread (Cheurprakobkit & Bartsch, 2005;Schreck et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…As such, it further underscored the most widespread sentiment among this existing literature-more rigorous research is required in order to assess the utility of these security tactics and justify their expense (Barrios, 2000;Cheurprakobkit & Bartsch, 2005;Juvonen, 2001;Schreck et al, 2003;Skiba, 2000). Only after such evaluations can school officials make informed decisions about the most effective approaches to address their crime problems.…”
Section: School Crime Preventionmentioning
confidence: 93%
See 2 more Smart Citations